2000
DOI: 10.1577/1548-8667(2000)012<0301:vcotbs>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Comparison of Three Buhl-Subtype Isolates of Infectious Pancreatic Necrosis Virus in Brook Trout Fry

Abstract: Infectious pancreatic necrosis virus (IPNV) is an important aquatic pathogen that can cause high mortality in populations of young salmonids. To determine the molecular basis of virulence, the fry of brook trout Salvelinus fontinalis were experimentally infected with three different A 1 -serotype, Buhl-subtype isolates of IPNV. The three isolates were selected on the basis of results of previously completed virulence assays, which indicated that the isolates had substantially differing virulence levels. To con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 18 publications
6
62
1
1
Order By: Relevance
“…This result is also in accordance with that of Sano et al (1992), who generated reassortants between virulent and avirulent strains of 2 different serotypes and demonstrated that the virulence of IPNV is associated with Segment A. Similarly, Bruslind & Reno (2000) found 2 amino acid differences in the VP2 at Positions 217 and 286 between the virulent and avirulent Buhl-subtype isolates of IPNV. VP2 is a major capsid protein and is responsible for the production of type-specific monoclonal antibodies (Nicholson 1993).…”
Section: Molecular Characterization Of Ipnv Isolatessupporting
confidence: 88%
See 1 more Smart Citation
“…This result is also in accordance with that of Sano et al (1992), who generated reassortants between virulent and avirulent strains of 2 different serotypes and demonstrated that the virulence of IPNV is associated with Segment A. Similarly, Bruslind & Reno (2000) found 2 amino acid differences in the VP2 at Positions 217 and 286 between the virulent and avirulent Buhl-subtype isolates of IPNV. VP2 is a major capsid protein and is responsible for the production of type-specific monoclonal antibodies (Nicholson 1993).…”
Section: Molecular Characterization Of Ipnv Isolatessupporting
confidence: 88%
“…Since virulence of IPNV has been associated with Segment A (Sano et al 1992), there may be differences at the molecular level within Segment A that makes the closely related isolates of IPNV so varied in their virulence. Recently, Bruslind & Reno (2000) identified 2 amino acid differences within the VP2 region of a virulent and avirulent Buhl strain of IPNV that was used to infect brook trout fry. However, there are no reports regarding the virulence of Sp serotype of IPNV.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are relatively few studies on the virulence factors of IPNV, and they are mainly focused on the connection of virulence to specific regions and residues of the genomic sequence (Sano et al, 1992;Bruslind & Reno, 2000;Santi et al, 2004;Shivappa et al, 2004;Song et al, 2005). Another well-known determinant of virulence is reassortment (Schrauwen et al, 2014), which has been suggested to be responsible for the existence of virulent variants among other viruses (Cárdenas et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (Bruslind & Reno 2000, Santi et al 2004, Shivappa et al 2004) have reported the presence of threonine and alanine at positions 217 and 221 of virulent strains, whereas low virulent strains have a proline and alanine at the same residues. As seen in Fig.…”
Section: Phylogenetic Analysismentioning
confidence: 99%